PELATIHAN PEMANFAATAN INTERNET DIBIDANG E-COMMERCE DALAM MENINGKATKAN JANGKAUAN PEMASARAN PRODUK UMKM DESA PAMULIHAN KECAMATAN SUBANG - Krisdiawan, Rio Andriyat; Yulyanto, Yulyanto (Empowerment, 2020)
UMKM (Micro, Small and Medium Enterprises) are productive businesses that are needed by individuals and business entities that have fulfilled the criteria as micro businesses. UMKM are distributed in full, each covering micro, small and medium enterprises according to law No. 20 of 2008. When the economic conditions in the village are developed and independent, the community will prosper. Pam Recovery Village has good potential, approved yields, agriculture, and animal husbandry. The economic condition of the pamovery village is supported by market activities and the release away from shipping is less strategic in marketing products. The development of the internet and technology, such as marketing media, known as e-commerce. How can the potential of villages that have been managed in the presence of UMKM be known to the wider community, one of them by utilizing e-commerce media. The focus of community service in the Pam Recovery village in the Kuningan regency that helps and provides assistance in using e-commerce media for UMKM to improve MSME marketing products that are broader, creative and innovative, can improve the livelihoods of the people of the recovery village.Keywords: UMKM (Micro, Small and Medium Enterprises), e-commerce